2020
DOI: 10.1590/0100-29452020628
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area estimation of Anacardium humile

Abstract: The Anacardium humile A. St.- Hil. fruit tree has productive potential, being their fruits appreciated in the Cerrado region for having characteristic flavor, however, this species is still exploited in an extractive way, being necessary studies for its domestication. The aim of this work was to estimate the leaf area of Anacardium humile. One hundred leaves were collected in the biological collection from a genetic resources field and evaluated for length, width and fresh weight, and scanned at resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Thus, the present study's sample size (number of leaves = 300) is adequate for estimating the leaf area of T. populnea using linear dimensions of the leaf limbs. Other research has also recorded greater variability for the product between length and width (Gomes et al 2020), the product between length and length (Ribeiro et al 2020b), the product between width and width (Oliveira et al 2019b), and observed leaf area (Donato et al 2020). The kurtosis coefficients of the variables of the present study showed that the frequency distribution was flatter than the normal distribution (Ribeiro et al 2020a).…”
Section: Discussionsupporting
confidence: 55%
“…Thus, the present study's sample size (number of leaves = 300) is adequate for estimating the leaf area of T. populnea using linear dimensions of the leaf limbs. Other research has also recorded greater variability for the product between length and width (Gomes et al 2020), the product between length and length (Ribeiro et al 2020b), the product between width and width (Oliveira et al 2019b), and observed leaf area (Donato et al 2020). The kurtosis coefficients of the variables of the present study showed that the frequency distribution was flatter than the normal distribution (Ribeiro et al 2020a).…”
Section: Discussionsupporting
confidence: 55%
“…Wide data variability is critical in regression model studies to estimate plant leaf area (LA) (Gomes et al, 2020), since the high variability of the data allows the estimation of more representative models and more accurate equations that can be applied to leaves of different shapes and sizes (Cargnelutti Filho et al, 2021). Direct collection of LA data necessitates a considerable number of leaf measurements, making it an expensive, time-consuming, destructive, and equipmentintensive endeavor.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, linear models are the most used to estimate the leaf area of agricultural and forest species (Gomes et al 2020, Goergen et al 2021, Hernandéz-Fernandez et al 2021, Mela et al 2022). However, it is assumed that these models are used with losses in precision, which often occurs due to the high values of the intercepts (β0) of the regression line (Santos et al 2021).…”
Section: Discussionmentioning
confidence: 99%